2014
DOI: 10.4103/1793-5482.146605
|View full text |Cite
|
Sign up to set email alerts
|

Factors prognosticating the outcome of decompressive craniectomy in severe traumatic brain injury: A Malaysian experience

Abstract: Objective: The objective of this prospective cohort study was to analyse the characteristics of severe Traumatic Brain Injury (TBI) in a regional trauma centre Hospital Kuala Lumpur (HKL) along with its impact of various prognostic factors post Decompressive Craniectomy (DC). Materials and Methods: Duration of the study was of 13 months in HKL. 110 consecutive patients undergoing DC and remained in our centre were recruited. They were then analysed categorically with standard analytical software. Results: Age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies. (25) found that after DC, there was significant improvement in the overall stability in ICU with stability of blood pressure, CPP, pulse rates and oxygen saturation, and postoperative ICP monitoring in the immediate within 24 hours and within 24-48 hours period showed significant decrease. Recently, some studies.…”
Section: Resultsmentioning
confidence: 90%
“…Some studies. (25) found that after DC, there was significant improvement in the overall stability in ICU with stability of blood pressure, CPP, pulse rates and oxygen saturation, and postoperative ICP monitoring in the immediate within 24 hours and within 24-48 hours period showed significant decrease. Recently, some studies.…”
Section: Resultsmentioning
confidence: 90%